2007
DOI: 10.1007/bf02686117
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of histone deacetylases 1–11 in the rat brain

Abstract: Although protein phosphorylation has been characterized more extensively, modulation of the acetylation state of signaling molecules is now being recognized as a key means of signal transduction. The enzymes responsible for mediating these changes include histone acetyl transferases and histone deacetylases (HDACs). Members of the HDAC family of enzymes have been identified as potential therapeutic targets for diseases ranging from cancer to ischemia and neurodegeneration. We initiated a project to conduct com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
301
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 317 publications
(315 citation statements)
references
References 46 publications
12
301
2
Order By: Relevance
“…This effect is likely because of specificity of HDACi 4b for particular HDAC isoforms, of which at least 11 are expressed in the rodent brain (29). These findings are also consistent with previous studies indicating that commercially available HDAC inhibitors can have both positive and negative effects on gene expression (reviewed in ref.…”
Section: Discussionsupporting
confidence: 91%
“…This effect is likely because of specificity of HDACi 4b for particular HDAC isoforms, of which at least 11 are expressed in the rodent brain (29). These findings are also consistent with previous studies indicating that commercially available HDAC inhibitors can have both positive and negative effects on gene expression (reviewed in ref.…”
Section: Discussionsupporting
confidence: 91%
“…In this study, we used contextual fear conditioning, a hippocampus-dependent task. Several HDAC isoforms are highly expressed in this brain regions (Broide et al, 2007). Using synthetic substrates that enable one to distinguish between class I and class II HDAC activities (Jones et al, 2008; SJ Haggarty, Personal Communication), we found that the HDACi's used in this study predominantly target the deacetylase activity of class I HDAC isoforms (HDAC1,2,3,8), with HDAC6, a class IIb isoform, also being targeted by SAHA (Table 1).…”
Section: Discussionmentioning
confidence: 75%
“…66 Histone Deacetylases Knowledge on HDACs and their role in the ischemic as well as in the healthy brain of rodent models is accumulating. Brain maps with expression analyses of HDACs are now available for mice, 67 rats, 68 and also humans (Website: r2012 Allen Institute for Brain Science. Allen Human Brain Atlas (Internet).…”
Section: Dna Methylationmentioning
confidence: 99%